Heat transfer in process engineering - Cao, Eduardo. 4 0 16; 5 (New York : McGraw-Hill, 2010)
Discusses various principles in heat transfer, covering design applications in process engineering for chemical, petro-chemical, and refining equipment, with information on analytical and empirical methods; efficient use of design software; troubleshooting; and complying with standards.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Transmission.;Transmission. -- Heat;Chemical processes.;Chemical engineering.;Heat exchangers.;Heat;Chemical reactions.;Chemical engineering; 20; 2